Manajemen Perpustakaan dalam Meningkatkan Minat Baca Peserta Didik - Khoirun Isnawan; Inom Nasution; Budi Budi (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The purpose of this study is to find out: 1) How is the library management system in MTs Negeri 2 Medan, 2) What are the interests of students in MTs Negeri 2 Medan, 3) What are the obstacles and obstacles of the library management in increasing students' interest in reading at MTs Negeri 2 Medan. The research design used in this study is Qualitative with a case study approach. The information in this study is the Head of the Library and library staff. The data collection techniques used are observation, interviews, and documentation studies. The data analysis used is data analysis from Miles & Huberman which includes data reduction, data presentation, and conclusion drawn, while the validity of the data validity guarantor is carried out by focusing on trust, distraction, dependence, and certainty. The results of this study show that: 1) the management function applied to the library is quite good, but in the future it will continue to be updated and developed, 2) the reading interest of students at MTs Negeri 2 Medan is quite high, they are able to find new things just by reading books in the school library, 3) The obstacles faced by the library are not too difficult, but should not be left unchecked. The library will always update the library management system so that students do not get bored of going to the library to learn and look for new things. The low interest in reading among students is due to technological advances and the misuse of technology. This is due to the lack of supervision from parents over their children which causes their children to always play with electronic devices and abandon positive activities such as reading books.